Effects of Soil Properties and Operational Variables on the Compactibility of a Sandy Loam Soil - Audu, D.; Balogun, O. S.; Adeniji, F. A.; Musa, Y. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The evaluation of an empirical equation for the determination of degree of compaction of a sandy loam soil was carried out using seven soil physical properties and four compaction operational variables. The soil used was obtained from a borrow pit in Gombe. Five levels of compactive effort, E/A, using a drop-weight type compactor varying from 107.91 to 539.55 Nm was used to compact each of seven pairs of embankment and slice thicknesses (Z, z respectively) with Z varying from 210 to 450 mm and z from 30 to 210 mm. The developed empirical equation, π1 = Gπ2k in which π1 is the dimensionless degree of compaction and π2 is a dimensionless combination of the soil properties and the compaction operational variables, has a very high coefficient of determination, r2 varying from 98.8% to 98.9%. G and k are each polynomial functions of compactive effort per loading, eL. that is, G = αGeL2+βG eL + λG and k=αkeL2+βkeL+ λk. The values of the respective α, β and λ are highly statistically significant at 99.95 confidence level. The “dependent” variables (G and k) are highly correlated at 99.95% confidence level of statistical significance with the “independent” variable (eL). The multivariate expression of the degree of compaction obtained in this study shows that compaction depends, not only on cumulative compactive effort, E/A, but also on the compactive effort per loading (eL), embankment and slice thicknesses (Z and z respectively) as well as on easy-to-measure soil properties (i.e. soil texture, soil uniformity coefficient, antecedent soil moisture and antecedent bulk density).